Corporate Governance Mechanisms and Carbon Emission Disclosure - Yasa, Ferina Khusumadewi; I Putu Sudana (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
Carbon emission disclosure is one of the material topics in sustainability report. The research was conducted to determine the impact of corporate governance mechanisms on carbon emission disclosure among energy sector companies listed on the Indonesia Stock Exchange. The analysis is based on 183 sustainability reports from the 2020–2023 period. Data were collected using the documentation method, and multiple linear regression analysis was conducted using SPSS software. The findings indicate that board size and audit committee have a positive influence on carbon emission disclosure, aligning with agency theory and corporate governance principles. Conversely, institutional ownership, managerial ownership, and the proportion of independent commissioners do not exhibit a significant effect on carbon emission disclosure.